Diagnostic Value of Plasma Long Non-coding SLC26A4 Antisense RNA 1 Combined with Magnetic Resonance Imaging in Rectal Cancer - Li, Zhiqian; Pu, Mei; Zhou, Peng; Zhang, Tao; Xu, Yang; Zhang, Yusui (Turkish Journal of Gastroenterology, 2024)
Background/Aims: The prevalence of rectal cancer is increasing every year due to changes in living and eating habits. Early diagnosis contributes to the treatment and survival of patients. This study investigated the feasibility of employing SLC26A4-AS1 combined with magnetic resonance imaging (MRI) for diagnosing rectal cancer. Materials and Methods: The current study involved 125 patients with rectal cancer and an equal number of healthy individuals. The study focused on assessing the relationship between SLC26A4-AS1 expression and clinical data among patients with rectal cancer by analyzing the expression levels. MRI blood perfusion parameters (Ktrans, Kep, Ve, and incremental area under the curve (iAUC)) were measured in the patients with rectal cancer. The regulation of SLC26A4-AS1 on the biological function of rectal cancer cells was analyzed by Cell Counting Kit-8 (CCK-8) method, flow cytometry, and Transwell assay. Furthermore, luciferase activity assays and RNA-binding protein immunoprecipitation assay (RIP) were conducted to elucidate the relationship between SLC26A4-AS1 and microRNA-3174 (miR-3174). Results: A significant reduction in SLC26A4-AS1 expression was observed in rectal cancer alongside a significant increase in miR-3174 levels. SLC26A4-AS1 expression was negatively correlated with Ktrans and Kep values, but not with Ve or iAUC values. Cell experiments confirmed the inhibitory effect of SLC26A4-AS1 overexpression on the growth of rectal cancer cells. Additionally, SLC26A4-AS1 sponged miR-3174 mediated the progression of rectal cancer. The enriched miR-3174 may counteract the suppression of the biological activity of oe-SLC26A4-AS1 on rectal cancer cells. Conclusion: SLC26A4-AS1 may serve as a diagnostic tool for rectal cancer, mediating tumor progression by directly targeting miR-3174. Cite this article as: Li Z, Pu M, Zhou P, Zhang T, Xu Y, Zhang Y. Diagnostic value of plasma long non-coding SLC26A4 antisense RNA 1 combined with magnetic resonance imaging in rectal cancer. Turk J Gastroenterol. 2024;35(12):900-908.